Potential Anti-Aging Substances Derived from Seaweeds - Cao, Lei; Lee, Sang Gil; Lim, Kwon Taek; Kim, Hyeung-Rak (Marine drugs, 2020)
Aging is a major risk factor for many chronic diseases, such as cancer, cardiovascular disease, and diabetes. The exact mechanisms underlying the aging process are not fully elucidated. However, a growing body of evidence suggests that several pathways, such as sirtuin, AMP-activated protein kinase, insulin-like growth factor, autophagy, and nuclear factor erythroid 2-related factor 2 play critical roles in regulating aging. Furthermore, genetic or dietary interventions of these pathways can extend lifespan by delaying the aging process. Seaweeds are a food source rich in many nutrients, including fibers, polyunsaturated fatty acids, vitamins, minerals, and other bioactive compounds. The health benefits of seaweeds include, but are not limited to, antioxidant, anti-inflammatory, and anti-obese activities. Interestingly, a body of studies shows that some seaweed-derived extracts or isolated compounds, can modulate these aging-regulating pathways or even extend lifespans of various animal models. However, few such studies have been conducted on higher animals or even humans. In this review, we focused on potential anti-aging bioactive substances in seaweeds that have been studied in cells and animals mainly based on their anti-aging cellular and molecular mechanisms.